PEMISAHAN BERKAS PERKARA (SPLITSING) DALAM TINDAK PIDANA KORUPSI PERSPEKTIF HUKUM ISLAM - Manik, Khatherine Sesilia; Putri, Shellya Eka; Simatupang, Septian Arjuanda Putra; Sianipar, Tiominar; Siahaan, Parlaungan Gabriel; Lbn Batu, Dewi Pika (IAIN BONE, 2023)
Splitting a case file is defined as the act of creating a new case file with more than one defendant. The purpose of the research is to find out the rationale for splitting cases, the legal basis, the impact and challenges in the implementation of splitting cases. The method used in this research is descriptive normative legal research with data collection techniques through observation at the Medan District Court and collection of written references. Splitsing is regulated in the provisions of Article 142 of the Criminal Procedure Code, but in the case of corruption in the Medan District Court it is true that the prosecutor split the case but in the trial the case was merged in accordance with the provisions of Article 141 of the Criminal Procedure Code, this was done so as not to conflict with the legal principle of contante justitie (fast, simple and low cost justice). Splitting will only complicate and slow down the trial process and even cause convoluted trials so that the principle of contante justitie is not fulfilled. In addition to the impact of splitsing, there are also challenges in its implementation, namely the possibility of defendants in other cases helping each other in their testimony so as not to incriminate the final decision of the crime and the violation of the defendant's human rights, namely the principle of non-self-incrimination.